Etnomatematika pada Kain Tenun Ikat Oba Agi Oba Pete dalam Masyarakat Nagekeo Nusa Tenggara Timur - Baidawi, Muhammad; Khasanah, Fitria; Una, Angela Merici Wea (JRPM (Jurnal Review Pembelajaran Matematika), 2023)
The purpose of this study is to describe the ethnomathematics contained in the oba agi oba pete woven cloth and its buying and selling transactions in the Nagekeo community. This research is qualitative research with the type of ethnographic research. The subjects in this study were the Nagekeo people who work as weavers and sellers of woven woven fabrics. The results of the study found that the history of woven cloth is not known with certainty, there are flat wake concepts in the form of squares, rectangles, triangles, and rhombuses in the woven cloth motifs. In the buying and selling transactions of woven woven fabrics, the Nagekeo community used to use addition, subtraction, multiplication, and division strategies. The Nagekeo people in buying and selling transactions use the barter system. The community measures woven fabrics using fathoms and spans.